Orientation of whole bone samples of small rodents matters during bending tests. (January 2017) - Ferreño, Diego; Sainz-Aja, José A.; Carrascal, Isidro A.; Diego, Soraya; Ruiz, Estela; Casado, José A.; Riancho, José A.; Sañudo, Carolina; Gutiérrez-Solana, Federico
Abstract: The influence of the orientation of rat bones on their mechanical response is analyzed in this research. 28 femora obtained from 14 Sprague-Dawley rats were subjected to three-point bending tests, comparing the anteroposterior and posteroanterior orientations. The results show that the whole-bone loading capacity of the femora tested in the posteroanterior orientation clearly exceeds that of the anteroposterior oriented bones. Likewise, the intrinsic (tissue-level) loading capacity of the bones tested in the posteroanterior orientation is manifestly higher than that of the bones tested in the opposite direction. The analysis carried out shows that applying beam theory for symmetric cross-sections leads to underestimating the stress state in the cross-section. In this sense, it is generally recommendable to use the non-symmetric beam theory in order to obtain the normal stresses during bending tests. The geometric, intrinsic and global changes resulting from the orientation of the bones was assessed, finding out that it is the variation in the intrinsic properties which explains the change measured in the whole-bone properties. The experimental scope was increased, including 8 additional femora on which a series of Vickers tests were carried out in the anterior and posterior regions of the cross-section. In all cases the hardness obtained in the anterior region is larger than in the posterior region. This result confirms that the mechanical properties of the bone tissue depend on its position in the cross-section and provides a reliable explanation to understand the response of the bones when subjected to bending tests. These results stress the importance of reporting the orientation of the bones in any scientific paper because, otherwise, it would be impossible to properly assess its impact and relevance.